Time Management and Its Implementation in Daily Life (Study of Surah Al 'Ashr) - Kurniawan, Ade; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2025)
Humans know time in every life, with the passage of time, humans encounter many experiences in the surrounding environment that can be used as material for thinking to improve their future. In explaining the concept of time management and its implementation in Surah al-'Ashr with the tahlili method which explores the meaning of each vocabulary referring to Arabic rules, such as nahwu Sharaf, balaghah, and semantics. In addition, it will discuss the interpretation of the scholars. Then continued to explore the aspects of maqashidi, education, and wisdom. With the explanation of the concept of time in Surah Al-'Ashr, humans can take lessons to make the best use of time. This is so that humans avoid losses both in this world and in the hereafter. Scholars differ in their interpretation of time, the first opinion says that time includes the steps and movements contained in it, the second opinion says that time is the time when the Asar prayer is carried out, the third opinion says that time is the presence of the Prophet Muhammad in this life. The word of Allah SWT in Surah Al-'Ashr illustrates that the condition of human beings is really at a disadvantage except for those who believe, those who do good deeds, and those who advise each other in truth and patience. To realize the implementation of the best time in life in the world, humans must maximize their efforts and prayers so that every time is guided by Allah SWT, the Lord of the Universe.